Measuring virtual learning environment success from the teacher’s perspective: Scale development and validation - Awang, Hapini; Mat Aji, Zahurin; Sheik Osman, Wan Rozaini (IP Publishing LLC, 2018)
This paper reports on the development of an instrument designed to measure the VLE success (VLES) amongst teachers. The items for VLES instrument were constructed in several steps including items’ face validation, content validation and reliability analysis. Forty-five final items have been produced after the analyses, with the deletion of 33 initial items. This validated VLES scale will be useful for future researchers in developing and testing VLE models or theories while at the same time will provide the tool for VLE stakeholders to evaluate the implementation from the teachers’ point of view.